A direct calibration of the IRX–β relation in Lyman-break Galaxies at z = 3–5. Issue 4 (12th June 2018) - Koprowski, M P; Coppin, K E K; Geach, J E; McLure, R J; Almaini, O; Blain, A W; Bremer, M; Bourne, N; Chapman, S C; Conselice, C J; Dunlop, J S; Farrah, D; et al.
ABSTRACT: We use a sample of 4209 Lyman-break galaxies (LBGs) at z ≃ 3, 4, and 5 in the UKIRT Infrared Deep Sky Survey Ultra Deep Survey field to investigate the relationship between the observed slope of the stellar continuum emission in the ultraviolet, β, and the thermal dust emission, as quantified via the so-called 'infrared excess' (IRX ≡ L IR / L UV ). Through a stacking analysis, we directly measure the 850-$μ$ m flux density of LBGs in our deep (0.9 mJy) James Clerk Maxwell Telescope SCUBA-2 850-${\rm μ m}$ map as well as deep public Herschel /SPIRE 250-, 350-, and 500-${\rm μ m}$ imaging. We establish functional forms for the IRX–β relation to z ∼ 5, confirming that there is no significant redshift evolution of the relation, and that the resulting average IRX–β curve is consistent with a Calzetti-like attenuation law. Comparing our results with recent works in the literature, we confirm that discrepancies in the slope of the IRX–β relation are driven by biases in the methodology used to determine the ultraviolet slopes. Consistent results are found when IRX–β is evaluated by stacking in bins of stellar mass, and we argue that the near-linear IRX– M ⋆ relationship is a better proxy for correcting observed ultraviolet luminosities to total star formation rates, provided an accurate handle on M ⋆ and also gives clues as to the physical driver of the role of dust-obscured star formation in high-redshift galaxies.